2020
DOI: 10.1101/2020.03.30.009472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new mutant mouse model lacking mitochondrial-associated CB1receptor

Abstract: The idea that the effects of drugs largely depend on subcellular target location is emerging as a novel predictive factor of their beneficial or adverse outcomes. G protein-coupled type-1 cannabinoid receptors (CB 1 ) are regulators of several brain functions as well as the main targets of cannabinoid-based medicines.Besides their classical location at plasma membranes, CB 1 receptors are present at different locations within cells, including in association to mitochondrial membranes (mtCB 1 ). Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As expected (Navarrete and Araque, 2010), neuronal depolarization induced an increase in the success rate in 9 of 19 distal neurons derived from wild-type animals (47.4%; Figures 4B-4E), without changes in the amplitude of evoked excitatory post-synaptic potentials (EPSCs; Figure 4B; Figure S4A), thereby indicating the occurrence of LSP. We then used a recently generated knockin (KI) mouse mutant line in which the DN22-CB 1 sequence replaces the wild-type CB 1 gene (DN22-CB 1 -KI mice; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021). These mutants lack the anatomical association of the CB 1 protein with mitochondria and do not display typical in vivo and ex vivo mitochondrialrelated effects of cannabinoids (e.g., decrease of cellular respiration and amnesic effects; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021).…”
Section: Physiological Role Of Mtcb 1 Receptors In Astrocyte-dependent Synaptic Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected (Navarrete and Araque, 2010), neuronal depolarization induced an increase in the success rate in 9 of 19 distal neurons derived from wild-type animals (47.4%; Figures 4B-4E), without changes in the amplitude of evoked excitatory post-synaptic potentials (EPSCs; Figure 4B; Figure S4A), thereby indicating the occurrence of LSP. We then used a recently generated knockin (KI) mouse mutant line in which the DN22-CB 1 sequence replaces the wild-type CB 1 gene (DN22-CB 1 -KI mice; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021). These mutants lack the anatomical association of the CB 1 protein with mitochondria and do not display typical in vivo and ex vivo mitochondrialrelated effects of cannabinoids (e.g., decrease of cellular respiration and amnesic effects; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021).…”
Section: Physiological Role Of Mtcb 1 Receptors In Astrocyte-dependent Synaptic Integrationmentioning
confidence: 99%
“…We then used a recently generated knockin (KI) mouse mutant line in which the DN22-CB 1 sequence replaces the wild-type CB 1 gene (DN22-CB 1 -KI mice; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021). These mutants lack the anatomical association of the CB 1 protein with mitochondria and do not display typical in vivo and ex vivo mitochondrialrelated effects of cannabinoids (e.g., decrease of cellular respiration and amnesic effects; Pagano Zottola et al, 2020;Soria-Gomez et al, 2021). However, the mutant mice maintain other functions of CB 1 receptors, such as the pharmacological activation of G protein signaling or the physiological regulation of hippocampal inhibitory neurotransmission (Pagano Zottola et al, 2020;Soria-Gomez et al, 2021).…”
Section: Physiological Role Of Mtcb 1 Receptors In Astrocyte-dependent Synaptic Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of systemic and peripheral CB1 knock-out mice has been implemented for a while and there are more and more studies using genetically modified specimens [ 35 , 36 , 41 , 42 ]. Our workgroup had previously shown interest in studying endocannabinoid signaling in skeletal muscle and we demonstrated that sarcoplasmic Ca 2+ release in adult and cultured mammalian skeletal muscles is affected and regulated by the ECS [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of a mouse model including a mutated CB1R unable to bind pregnenolone, as shown in our in vitro model, 73 should allow us to elucidate new endogenous mechanisms of CB1 regulation by pregnenolone. Genetic tools are indeed key to unravelling new CB1‐mediated functions, such as exploring the in vivo effects of mtCB1 receptors in DN22‐CB1 and DN22‐CB1‐KI mice 125,191 . Targeting the pregnenolone‐CB1 binding pocket may represent an exciting opportunity to shed light on new functions for steroids with respect to regulating GPCR activity.…”
Section: Discussionmentioning
confidence: 99%